An Investigation into the Teaching Practices and Material Effects on Student Outcomes: A Case Study from Oman - Sarath Withanarachchi Samaranayake; Suneeta Kositchaivat; Vachira Jantarach (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
Acquisition of an additional language is assumed to involve several internal and external factors for the learner. Among external factors, instructional procedures and materials are vital in helping learners master L2 skills. This study investigates how the instructor’s instructional variables and in-house materials influence tertiary-level Omani students’ academic writing proficiency in Omani technological education. The study used a quasi-experimental research design in which two treatment (N = 60) and comparison (N = 60) groups and two instructors were included. The researchers selected participants for the current study using a random purposive sampling technique. The treatment groups received writing instruction via in-house materials, while the comparison groups were instructed using the prescribed textbook by two instructors for two semesters. The study employed four research instruments (a pretest, mid-semester, final exam, and intervention instrument) to gather data, which were analyzed using descriptive and non-parametric tests (Mann-Whitney U test). The results of an MNOVA test that comprised three components (class, instructor, and comparison or treatment group) revealed statistically significant effects on all three factors; class (F = 6.18, p =.001), instructor (F = 2.83, p =.001), and group (F =1. 15, p =.001), indicating that an instructor’s effective instructional procedures and in-house materials, influenced the study groups’ outcomes. Given the findings, it can be concluded that different instructional strategies and in-house materials can affect students’ academic writing proficiency differently.